Address on the opening Alexander von Humboldt Season in Quito, Ecuador, on 13 February 2019 (With an introduction by Ottmar Ette) - Frank-Walter Steinmeier, Federal President (HiN – Alejandro de Humboldt en la Red. Revista internacional de estudios humboldtianos, 2019)
No abstract available.